Trends in water quality in the Alqueva irrigation area and its potential effects on soil structure and on crop yields - Tomaz, Alexandra (2019)
One of the major threats to the sustainability of irrigated agriculture is the risk of land salinization, due to the reduction in water quality and to the increase of soil salt concentrations leading to crop yield reductions. Therefore, monitoring salinity status of agricultural water resources is increasingly important to prevent soil salinization processes. The Alqueva reservoir constitutes the most important water supply source in Alentejo, a region where agriculture is one of the main activities. Based on the physicochemical characteristics of water collected in nine sampling sites along the Alqueva reservoir, the evolution of water quality for irrigation, and its potential effects on soil structure and on crop yields, was assessed throughout two sampling campaigns, 2006-2007 and 2011-2012. The Maas-Hoffman (MH) and the van Genuchten-Hoffman (GH) models were used to determine the relative yield (Yr) for the main crops grown in the Alqueva irrigation area. Overall, from 2006-2007 to 2011-2012, the results indicated an increment of the ionic concentrations at the water body, more significant for sodium (+55%), chloride (+44%), and magnesium (+30%). The sodium adsorption rate values (SAR) showed an average increase of 36%. The assessment of water quality for agriculture performed for both campaigns, using the FAO guidelines, showed slight to moderate risk of reduced infiltration rates in every site and date, which is particularly significant in fine textured soils, and whenever sprinkler irrigation systems are used. The water collected at some sites and dates had characteristics consistent with a slight to moderate risk of sodium and chloride toxicity when using sprinkler irrigation. The lower Yr estimates (85 to 89%) using both the MH and the GH models occurred for almond, table grape, pumpkin and onion, indicating that attention should be given to sensitive and moderately sensitive crops cultivated in the Alqueva irrigation area, especially in drought years.